2003
DOI: 10.1034/j.1399-6576.2003.00182.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different concentrations of levobupivacaine for post‐operative epidural analgesia

Abstract: The same dose of levobupivacaine provides an equal quality of analgesia in low or high volume continuous thoracic epidural infusion with reduced haemodynamic instability and nausea in the low volume/high concentration groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 33 publications
3
25
0
1
Order By: Relevance
“…23 Several studies have subsequently demonstrated identical sensory and motor blockade when using local anesthetic solutions of widely different concentrations but of equal drug dose. [2][3][4][5][6][7][8][9][10][11][12]24,25 Some studies even demonstrated improved postoperative analgesia with concentrated epidural local anesthetic infusions 9 and more profound motor block 3,4 and hypotension 3,4 when using dilute solutions. Conversely, other studies have been published that support the superiority of dilute epidural local anesthetics for diffuse low intensity analgesia, particularly in labor analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…23 Several studies have subsequently demonstrated identical sensory and motor blockade when using local anesthetic solutions of widely different concentrations but of equal drug dose. [2][3][4][5][6][7][8][9][10][11][12]24,25 Some studies even demonstrated improved postoperative analgesia with concentrated epidural local anesthetic infusions 9 and more profound motor block 3,4 and hypotension 3,4 when using dilute solutions. Conversely, other studies have been published that support the superiority of dilute epidural local anesthetics for diffuse low intensity analgesia, particularly in labor analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Verghese et al 4 demonstrated that a caudal block with HVLC is more effective than LVHC in reducing the peritoneal response caused by pulling of the spermatic cord during orchidopexy. They performed a caudal block with a fixed dose of 0.2% and 0.25% bupivacaine, but only produced a 20% difference in volume.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 When the total drug dose is fixed, it is uncertain whether the volume or concentration of local anaesthetic influences the spread and quality of caudal analgesia. 4,5 In children, there is limited data regarding the relative effects of volume and concentration of local anaesthetic solutions used for caudal analgesia and the conclusions are still under debate. 1,6,7 In addition, no study has assessed the spread of local anaesthetics and its related analgesic duration.…”
Section: Introductionmentioning
confidence: 99%
“…The ra ti o na le for such a com bi na ti on is a pu ta ti ve ad di ti ve or syner gis tic ef fect which will pro vi de ef fec ti ve anal ge si a with re du ced doses, and the re fo re re du ced si de ef fects of both drugs. 23,24 One of the ma in ad van ta ges of the pre ope ra ti vely ini ti a ted TE A was the sta bi lity of car dio vas cu lar pa ra me ters. The re we re no mar ked chan ges in me an ar te ri al blo od pres su re or he art rate in pos top-TE A gro up in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Du ring the first 48 h af ter the ope ra ti on, pa tients used the epi du ral PCA as des cri bed in the proto col and they we re qu es ti o ned abo ut the ir pa in at 1, 2,4,8,12,16,20,24,36 and 48 h at rest and coug hing by an ob ser ver blin ded to tre at ment gro ups using VAS and the re sults we re re cor ded. The to tal amo unt of anal ge sics the pa ti ent re ce i ved and the num ber of re qu ests for anal ge si a from the pump we re re cor ded.…”
Section: Ma Te Ri Al and Met Hodsmentioning
confidence: 99%